Análisis crítico – jurídico sobre la difusión de pornografía infantil y su afectación al desarrollo integral de los niños, niñas y adolescentes. 4 - Quilca Guaman, Joel Nahum (2024)
The spread of child pornography in the "Teodoro Gómez de la Torre" educational unit seriously affects the psychological, academic and social well-being of children and adolescents. Data shows that exposure to these contents causes anxiety, depression, trauma and problems in academic performance, in addition to deteriorating social relationships by generating withdrawn or aggressive behavior. Within the used methodology, it was a qualitative and quantitative study to collect data through a non-experimental design. The scope of the research is legal-explanatory, as theoretical level methods were used the Inductive-deductive, Dogmatic-legal and a Documentary Analysis, and as research techniques a questionnaire and interview to key informants were carried out. The interview was conducted differently for each informant to capture detailed perspectives on the effects of child pornography on students' psychological well-being, academic performance, and social relationships. The results of the analysis indicated that exposure could cause anxiety, depression, problems in academic performance and deterioration in social relationships. Based on these findings, it is recommended to implement preventive and educational programs in schools, train teaching staff and establish clear protocols for handling and reporting incidents related to child pornography. Furthermore, it is essential to improve the ongoing training of staff and provide specialized psychological support for victims, ensuring a comprehensive and coordinated response to protect minors and mitigate the effects of this problema.